(3GdEYdGe GdEbJUGOj (B/s - (3GdTeQj, fGXe NGdOs ((3GdCQOf(B- (3YeGf (B:s (3OGQ CSGeI ddfTQ h GdJhRjY ,s, 2012)
(3JYQja GdGYdGe hhXGFag bQGAI JMdjdjI (B- (3JYQja Yde GdEbJUGO h aQhYg(B- (3GdYhdeI GdGbJUGOjI(B- (3GdaUd GdNGeS jJMOK Yf hSGFd GdEYdGe h GdEYdGf (B---(3GdYdGbI h GdJCKjQs
(3HjHd(B.:211-220s
Keywords: (3GdEJUGd GdLeGgjQjs; (3GdEYdGe GdEbJUGOjs; (3GdEbJUGOs